2006
DOI: 10.1128/aem.00349-06
|View full text |Cite
|
Sign up to set email alerts
|

Marine and Freshwater Cyanophages in a Laurentian Great Lake: Evidence from Infectivity Assays and Molecular Analyses of g20 Genes

Abstract: While it is well established that viruses play an important role in the structure of marine microbial food webs, few studies have directly addressed their role in large lake systems. As part of an ongoing study of the microbial ecology of Lake Erie, we have examined the distribution and diversity of viruses in this system. One surprising result has been the pervasive distribution of cyanophages that infect the marine cyanobacterial isolate Synechococcus sp. strain WH7803. Viruses that lytically infect this cya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
85
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 49 publications
4
85
1
1
Order By: Relevance
“…Although several studies of conserved phage structural genes have clearly demonstrated that molecular approaches can be used to infer the community richness of viruses that infect freshwater algae (e.g. Wang & Chen 2004, Short & Suttle 2005, Wilhelm et al 2006, ours is the first report of genetic richness of freshwater viruses that infect eukaryotic algae.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies of conserved phage structural genes have clearly demonstrated that molecular approaches can be used to infer the community richness of viruses that infect freshwater algae (e.g. Wang & Chen 2004, Short & Suttle 2005, Wilhelm et al 2006, ours is the first report of genetic richness of freshwater viruses that infect eukaryotic algae.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, cyanomyoviruses are able to cross-infect a broad range of hosts, whereas cyanopodoviruses and cyanosiphoviruses are more host specific (Sullivan et al, 2003;Weigele et al, 2007;Wang and Chen, 2008). The genetic diversity of cyanomyoviruses in various aquatic environments has been explored extensively based on their conserved capsid gene (g20) (Fuller et al, 1998;Zhong et al, 2002;Wang and Chen, 2004;Filee et al, 2005;Short and Suttle, 2005;Wilhelm et al, 2006;Sullivan et al, 2008). In contrast, little is known about the diversity of cyanopodoviruses and cyanosiphoviruses.…”
Section: Introductionmentioning
confidence: 99%
“…Nearly 20 years ago, Proctor and Fuhrman (1990) reported that 1-3% of the cyanobacteria from diverse marine locations contained mature viral particles. Since then, viruses have been isolated using different groups of marine and freshwater picocyanobacteria, including Synechococcus and Prochlorococcus strains (Suttle and Chan, 1993;Waterbury and Valois, 1993;Wilson et al, 1993;Suttle, 2000;Lu et al, 2001;Sullivan et al, 2003;Sullivan et al, 2005;Wilhelm et al, 2006;Pope et al, 2007;Wang and Chen, 2008). It has been estimated that cyanophages may be responsible for approximately 5-14% of cyanobacterial mortality on a daily basis (Suttle and Chan, 1994;Binder 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The diversity of these myoviruses has been studied in some detail using PCR primers specific for the major capsid protein g20 (Fuller et al, 1998;Wilson et al, 1999;Zhong et al, 2002;Sandaa and Larsen, 2006;Sullivan et al, 2006Sullivan et al, , 2008Wilhelm et al, 2006).…”
Section: Introductionmentioning
confidence: 99%